On some brachypterous Encyrtidae (Hymenoptera: Chalcidoidea) from India, with description of four new species - Hayat, Mohammad; Zeya, Shahid Bin; Veenakumari, K. (Zootaxa, 2013)
Four new species of brachypterous Encyrtidae (Hymenoptera: Chalcidoidea) are described. These are: Cheiloneurus mandyanus Hayat, sp. nov., Encyrtus coorgensis Hayat & Zeya, sp. nov., Microterys atturensis Hayat, sp. nov. and Pseudectroma indicum Hayat & Zeya, sp. nov. The following species that exist either in brachypterous forms only or in both brachypterous and macropterous forms are recorded: Anomalicornia tenuicornis Mercet, Cheiloneurus bangalorensis (Subba Rao), C. quadricolor (Girault), Diversinervus cervantesi (Girault), Globulencyrtus politus (Hoffer), Indaphycus planus Hayat, Neodusmetia sangwani (Subba Rao), Prochiloneurus bolivari Mercet, Rhopus atys Noyes & Hayat and Sakencyrtus mirus Hayat. Globulencyrtus politus and P. bolivari are newly recorded from India. A diagnosis of Globulencyrtus, and redescriptions of G. politus, P. bolivari based on the Indian specimens and of the brachypterous forms of R. atys are given. The occurrence of brachyptery in the Encyrtidae is briefly noted together with a list of brachypterous species recorded from India.